Induced Pluripotent Stem Cells; New Tools for Investigating Molecular Mechanisms in Anorexia Nervosa - Maussion, Gilles; Demirova, Iveta; Gorwood, Philip; Ramoz, Nicolas (Frontiers in Nutrition, 2019)
Anorexia Nervosa (AN) is a dramatic psychiatric disorder characterized by dysregulations in food intake and reward processing, involving molecular and cellular changes in several peripheral cell types and central neuronal networks. Genomic and epigenomic analyses have allowed the identification of multiple genetic and epigenetic modifications highlighting the complex pathophysiology of AN. Behavioural and genetic rodent models have been used to recapitulate and investigate, with some limitations, the cellular and molecular changes that potentially underlie eating disorders. In the last five years, the use of induced-pluripotent stem cells, combined with CRISPR-Cas9 technology has led to the generation of specific neuronal cell sub-types engineered from human somatic samples, representing a powerful tool to complement observations made in human samples and data collected from animal models. Systems biology using induced-pluripotent stem cells has indeed proved to be a valuable approach for the study of metabolic disorders, in addition to neurodevelopmental and psychiatric disorders. The manuscript while reviewing the main findings related to the genetic, epigenetic and cellular bases of AN, will present how new studies published, or to be performed, in the field of IPSC-derived cells should improve our current understanding of the pathophysiology of AN, and provide potential therapeutic strategies addressing specific endophenotypes.